2021
DOI: 10.1007/s11013-021-09726-5
|View full text |Cite
|
Sign up to set email alerts
|

Feeling Seen, Being Heard: Perspectives of Patients Suffering from Mental Illness on the Possibility of Physician-Assisted Death in the Netherlands

Abstract: Physician-assisted death (PAD) for patients suffering from a mental illness is allowed in the Netherlands under certain conditions but is a very controversial topic, mainly discussed by ethicists and physicians. The voice of the patient is rarely included in the debate, so we know little about what their views on the topic are. We aim to understand the views of patients with mental illness and wish to die with regard to the possibility of PAD in the Netherlands. The data for this qualitative study were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 12 publications
2
19
0
Order By: Relevance
“…We found that a granted request for PAD was seen as validation of the severity of the suffering, both from the perspective of the bereaved as well as their social environment. A similar result was found in an interview study among patients with a PAD-request suffering from mental disorders, where patients were looking for recognition of their suffering (38). Expectedness of the death of the partner, lack of suffering of the partner at the time of dying, and presence of physician support may in part explain the protective effects of PAD against severe grief reactions.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…We found that a granted request for PAD was seen as validation of the severity of the suffering, both from the perspective of the bereaved as well as their social environment. A similar result was found in an interview study among patients with a PAD-request suffering from mental disorders, where patients were looking for recognition of their suffering (38). Expectedness of the death of the partner, lack of suffering of the partner at the time of dying, and presence of physician support may in part explain the protective effects of PAD against severe grief reactions.…”
Section: Discussionsupporting
confidence: 73%
“…For many bereaved partners, their loved one's death eventually was the only option, since their life was no longer bearable. This is in line with a previous study into considerations on PAD of patients suffering from a mental disorder (38). Furthermore, there is no consensus as to whether or not a suicide can be considered a choice.…”
Section: Finding the Right Wordssupporting
confidence: 80%
“…It also corresponds with the feeling of "treatment fatigue" that often appears to underly the MAiD request of patients with a psychiatric disorder. 14 Furthermore, a retrospective view on irremediability justifies the intuitive uneasiness that various psychiatrists reported with providing MAiD for patients who refuse treatment. Because the patient's history is central to establishing irremediability, treatment refusal can seriously hamper the psychiatrist's ability to make a meaningful claim about irremediability.…”
Section: Discussionmentioning
confidence: 99%
“…Our study did not capture the perspectives of patients and their families on irremediable psychiatric suffering in the context of MAiD, and future studies should explore this. 14,22 Future research should also focus on the views of psychiatrists from other countries and cultures.…”
Section: Limitationsmentioning
confidence: 99%
“…A Dutch study showed that the most frequent reasons for MAiD-NT were irreversibility, loss of control, emptiness and emotional flooding, freezing, social distancing, narcissistic wounds, confusion, and self-estrangement [32]. A further study showed that patients with psychiatric disorders reported autonomy and self-determination, ending the suffering, recognition as being persons, and dignified end-of-life as the main reasons to request MAiD-NT [33].…”
Section: Opinions and Attitudes Of People With Psychiatric Disordersmentioning
confidence: 99%